Covid-19 with Methicillin-Resistant Staphylococcus Aureus: Based on Two Cases in Diponegoro National Hospital - Dwi Retnoningrum; Setyo Gundi Pramudo; Taufik Eko Nugroho; Qonita Nur Qolby (JAI (Jurnal Anestesiologi Indonesia))
Background: Coronavirus disease 19 (COVID-19) has become pandemic in the world with a board spectrum of clinical presentation. Secondary infection of methicillin-resistant staphylococcus aureus (MRSA) affects morbidity and mortality in patients with COVID-19.